2014
DOI: 10.1111/1750-3841.12344
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti‐Inflammatory Activity of Selected Oxalate‐Degrading Probiotic Bacteria: Potential Applications in the Prevention and Treatment of Hyperoxaluria

Abstract: The oxalate-degrading activity of some probiotics and their capability to modulate the release of inflammation mediators could be exploited as a new nutraceutical and therapeutic approach for the treatment of oxalate accumulation and the related inflammatory state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Probiotic strains, studied in this work, were chosen exactly based on their immune-modulatory activity. In vitro efficacy of L. acidophilus LA-14 to modulate the human anti-inflammatory immune response has previously been investigated [ 28 ]; there is a preliminary evidence that probiotic supplementation of L. casei Shirota improved immunological parameters and reduced key inflammatory cytokine markers [ 29 ]. L. lactis NCDO 2118 has been used in the treatment of inflammatory bowel disease (IBD), since it was able to reduce IL-1 β -induced IL-8 secretion in Caco-2 cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic strains, studied in this work, were chosen exactly based on their immune-modulatory activity. In vitro efficacy of L. acidophilus LA-14 to modulate the human anti-inflammatory immune response has previously been investigated [ 28 ]; there is a preliminary evidence that probiotic supplementation of L. casei Shirota improved immunological parameters and reduced key inflammatory cytokine markers [ 29 ]. L. lactis NCDO 2118 has been used in the treatment of inflammatory bowel disease (IBD), since it was able to reduce IL-1 β -induced IL-8 secretion in Caco-2 cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] In particular, Lactobacillus plantarum exhibits various biological effects including antitumour, anticoagulant, antiviral, immune modulatory and anti-inflammatory, antidiabetic and antioxidant or free radical scavenging activity. [10][11][12][13] We reported that L. plantarum L67 isolated from infant faeces has a high survival rate at low pH values.…”
Section: Introductionmentioning
confidence: 99%
“…Uric acid stones are formed due to low urine output, excessive intake of proteins, especially red meat. These form in acidic urine and are not visible in a plain X-Ray (Giardina et al, 2014).…”
Section: Introductionmentioning
confidence: 97%